Human–wildlife conflict: Proximate predictors of aggression between humans and rhesus macaques in India. Issue 2 (28th October 2014) - Beisner, Brianne A.; Heagerty, Allison; Seil, Shannon K.; Balasubramaniam, Krishna N.; Atwill, Edward R.; Gupta, Brij K.; Tyagi, Praveen C.; Chauhan, Netrapal P.S.; Bonal, B.S.; Sinha, P.R.; McCowan, Brenda
ABSTRACT Macaques live in close contact with humans across South and Southeast Asia, and direct interaction is frequent. Aggressive contact is a concern in many locations, particularly among populations of rhesus and longtail macaques that co‐inhabit urbanized cities and towns with humans. We investigated the proximate factors influencing the occurrence of macaque aggression toward humans as well as human aggression toward macaques to determine the extent to which human behavior elicits macaque aggression and vice versa. We conducted a 3‐month study of four free‐ranging populations of rhesus macaques in Dehradun, India from October–December 2012, using event sampling to record all instances of human‐macaque interaction (N = 3120). Our results show that while human aggression was predicted by the potential for economic losses or damage, macaque aggression was influenced by aggressive or intimidating behavior by humans as well as recent rates of conspecific aggression. Further, adult female macaques participated in aggression more frequently than expected, whereas adult and subadult males participated as frequently as expected. Our analyses demonstrate that neither human nor macaque aggression is unprovoked. Rather, both humans and macaques are responding to one another's behavior. Mitigation of human‐primate conflict, and indeed other types of human‐wildlife conflict in such coupled systems, will require a holistic investigation of the ways in which each participant is responding to, and consequently altering, the behavior of the other. Am J Phys Anthropol 156:286–294, 2015. © 2014 Wiley Periodicals, Inc.